Beacon trust management system and fake data detection in vehicular ad‐hoc networks. Issue 5 (15th January 2019) - Arshad, Muhammad; Ullah, Zahid; Khalid, Muhammad; Ahmad, Naveed; Khalid, Waqar; Shahwar, Duri; Cao, Yue
Abstract : A vehicular ad‐hoc network is an emerged technology, where vehicles communicate with one another and Road Side Units. Vehicular ad‐hoc networks are categorised as a sub‐branch of mobile ad‐hoc networks, and they help in enhancing traffic efficiency and safety. Vehicular ad‐hoc networks facilitate communication by dissemination of messages relaying through vehicles. However, malicious nodes can propagate false safety alert in a network due to its malicious behaviour or selfishness. False messages in vehicular ad‐hoc networks can change drivers behaviour and create a disastrous situation in the network. Therefore, it is more important to thwart these false messages. The article presents a beacon trust management system and fake data detection (BTMS‐FDD) scheme. The trust management system uses speed and density information to establish a relationship with vicinity vehicles. The false safety event detection scheme uses relative safety and beacon messages to detect false safety event more accurately. For false safety events, a scheme uses position and speed information of beacon and safety‐related messages. To analyse the performance of proposed detection scheme, it is compared with ELIDV and host IDS schemes. The simulation results demonstrate that proposed malicious data detection scheme is better in terms of true positive, false positive and overhead.